Pengaruh Model Project-Based Learning Berbasis Deep Learning Terintegrasi Kecerdasan Buatan terhadap Kemampuan Berpikir Kritis dan Literasi Sains Mahasiswa PGSD - Dedi Holden Simbolon; Eka Kartika Silalahi; Rupina Magdalena br Tarigan (Postgraduate, University of Mataram, 2026)
This study examined the effect of an AI-integrated Deep Learning Project-Based Learning model on the critical thinking skills and scientific literacy of Primary School Teacher Education students at a university in Indonesia. A quasi-experimental non-equivalent control group design was employed involving 156 students, with 78 students in the experimental group and 78 students in the control group. Data were collected through critical thinking tests, scientific literacy tests, and a learning engagement questionnaire, then analysed using independent samples t-tests, N-Gain, Cohen’s d, and SEM-PLS. The experimental group achieved higher mean scores in critical thinking skills than the control group (84.28 vs. 71.33) and higher scientific literacy scores (83.10 vs. 71.50). The N-Gain values for critical thinking were 0.71 in the experimental group and 0.46 in the control group, while scientific literacy N-Gain values were 0.69 and 0.47, respectively. Cohen’s d values indicated very large effects for critical thinking skills (4.23) and scientific literacy (4.04). SEM-PLS showed positive relationships between the learning model and engagement (β = 0.72), engagement and critical thinking (β = 0.55), engagement and scientific literacy (β = 0.52), as well as direct effects on critical thinking (β = 0.68) and scientific literacy (β = 0.65). These findings indicate that the model supports meaningful, technology-enhanced learning.